Perlindungan Hukum Bagi Karyawan Notaris Yang Tidak Terdaftar BPJS Ketenagakerjaan Berdasarkan Undang-Undang No. 24 Tahun 2011 Tentang Badan Penyelenggara Jaminan Sosial - Shinurad, Duto Mahardiko; Huda, Miftahul (Fakultas Hukum Universitas Narotama, 2024)
Article 27 paragraph (2) of the 1945 Constitution mandates the government to provide protection for labor and a decent livelihood for humanity. Today's rapid business development has an impact on the need for notaries as officials who make authentic deeds. This authentic deed will later become evidence with full legal force in court. The result of the increasing need for notaries is the increasing number of notaries and notary offices which then open up jobs as notary employees. When looking at the legal relationship between notaries and notary employees, the employer is the notary and the workers are notary employees, while the notary office is a company. For this reason, the existing rules in Law no. 24 of 2011 concerning the Social Security Organizing Agency also apply to notary offices. Normative juridical legal research methods, or research done by looking at the laws and regulations that apply or are applied to a specific problem with 2 (two) approaches, namely: statute approach and conceptual approach, are the research method used to address the legal issues raised in this study. Primary and secondary legal resources were the sources of research materials employed in this study. The deduction method, which is the process of conducting research based on general principles to explain particular events or from general theories to concrete facts, was the analysis approach employed in the compilation of data for this study. The formulation of the problem in this paper is how the form of legal protection for notary employees who are not registered with the Employment BPJS based on Law no. 24 of 2011 concerning the Social Security Organizing Agency (BPJS) Keywords: Social Security, Worker, Notary